2020
DOI: 10.1101/2020.06.12.20127944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of SARS-CoV-2 in Breastmilk from 18 Infected Women

Abstract: To The Editor, Currently, the U.S. Centers for Disease Control and Prevention, American Academy of Pediatrics and the World Health Organization advise that women who are infected with SARS-CoV-2 may choose to breastfeed with appropriate protections to prevent transmission of the virus through respiratory droplets. However, the potential for exposure to SARS-CoV-2 through breastfeeding is currently unknown. To date, case reports on breastmilk samples from a total of 24 SARS-CoV-2-infected women have been publ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 6 publications
1
44
0
3
Order By: Relevance
“…However, the presence of the virus in human milk was not evaluated. Recently the presence of SARS-CoV-2 in breastmilk was evaluated in 18 infected women from delivery to 19 months, with only one sample found positive (19). These data are in accordance with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the presence of the virus in human milk was not evaluated. Recently the presence of SARS-CoV-2 in breastmilk was evaluated in 18 infected women from delivery to 19 months, with only one sample found positive (19). These data are in accordance with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, detection of SARS-CoV-2 RNA does not necessarily imply the presence of an infectious and active virus that can be transmitted via breastfeeding to infect the infant (19).…”
Section: Discussionmentioning
confidence: 99%
“…Samples of breastmilk from 18 women infected with SARS-CoV-2 were evaluated and although SARS-CoV-2 RNA was detected in one sample of milk, the follow-up culture of the same sample was negative. It is likely that the SARS-CoV-2 RNA that was found does not contain replication-competent virus and so is unlikely to infect an infant [20]. Findings from this group of cases suggest that there is currently no evidence to show that respiratory viruses can be transmitted through breast milk.…”
Section: Covid-19: the Disease Epidemiology And The Breastfeeding Popmentioning
confidence: 85%
“…To date, there is no sure evidence that novel severe acute respiratory Coronavirus Virus 2 (SARS-CoV-2) can be transferred through human milk (Auriti et al, 2020), although an intermittent excretion of the virus has been reported (Costa et al, 2020). Furthermore, detection of viral RNA by RT-PCR in human milk does not equate with infectivity (Chambers et al, 2020). Cold storage of SARS-COV-2 in human milk did not significantly change viral load over a 48 hr period according to a study in which the virus was experimentally inoculated into human milk samples (Walker et al, 2020).…”
Section: Universal Screening For Sars-cov-2 Of All Human Milk Bank Samentioning
confidence: 99%